ANALISIS RANTAI PASOK UNTUK PENGEMBANGAN PRODUK OLAHAN BUAH ANGGUR DI JAWA BARAT - Sriwana, Iphov Kumala; Pambudi, Hardian K.; Nurdiansyah, Yodi; Yakti, Suluh W. (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2023)
The opportunities for developing grapes on an agribusiness and agroindustry scale in Indonesia are very high but have not been widely implemented. The aim of this research is to analyze the obstacles to the development of the current downstream grape supply chain. To develop the downstream grape supply chain, the first step is to identify the sub-elements that are part of the affected sector elements, the obstacles that occur and the programs needed. Identification of sub elements is carried out using ISM. Based on the results of the Interpretive Structural Modeling (ISM) analysis, the results showed that the obstacles to the downstreaming of the wine supply chain were that it had not paid attention to farmers who were the most important actors, had not designed a quality assurance system which was a program that should have been designed from the start of downstream planning and didn’t pay attention to the availability of materials. standard which is the main obstacle that has not been implemented so far. These three sub-elements can be integrated for institutional design to make downstream activities easier.